2022
DOI: 10.3390/foods11111622
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Inflammatory Effects of Red Rice Bran Extract Ameliorate Type I Interferon Production via STING Pathway

Abstract: Type I interferons (IFNs-I) are inflammatory cytokines that play an essential role in the pathogenesis of inflammation and autoimmune diseases. Signaling through nucleic acid sensors causes the production of IFNs-I. A stimulator of interferon genes (STING) is a DNA sensor that signals transduction, leading to the production of IFNs-I after their activation. This study aims to determine the anti-inflammatory effects of red rice bran extract (RRBE) on macrophages through the activation of STING signaling. RAW264… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 64 publications
1
6
0
Order By: Relevance
“…Several factors can modulate the level of IFN-Is through IRF 3 via distinct ways, regulating the innate immune response and inhibiting pro-inflammatory signaling. For instance, red rice bran extract (RRBE) can inhibit the phosphorylation of STING, blocking the activation of IRF 3 to hinder initiation of IFN-Is signaling, which function as pro-inflammatory cytokines [ 108 ]. Additionally, the E3 ligase RNF 5 can also limit the signaling of IRF 3 through targeting STING, suppressing the production of IFN-Is, which instead promotes viral replication and abnormal inflammation development [ 109 ].…”
Section: Type I Interferon Signaling In Inflammationmentioning
confidence: 99%
“…Several factors can modulate the level of IFN-Is through IRF 3 via distinct ways, regulating the innate immune response and inhibiting pro-inflammatory signaling. For instance, red rice bran extract (RRBE) can inhibit the phosphorylation of STING, blocking the activation of IRF 3 to hinder initiation of IFN-Is signaling, which function as pro-inflammatory cytokines [ 108 ]. Additionally, the E3 ligase RNF 5 can also limit the signaling of IRF 3 through targeting STING, suppressing the production of IFN-Is, which instead promotes viral replication and abnormal inflammation development [ 109 ].…”
Section: Type I Interferon Signaling In Inflammationmentioning
confidence: 99%
“…The effect of rice bran oil niosomes of three different varieties has been studied on the expression of varying proinflammatory genes and found that the expression of IL‐1β and TNF‐α genes in the LPS‐stimulated THP‐1 monocytes was reduced (Jom et al, 2021). Onsa‐Ard et al (2022) investigated the anti‐inflammatory impact of red rice bran extract on the IFN‐I via the stimulation of interferon genes (STING) signaling. They observed the decreased phosphorylation of the STING gene, which reduces the Irf3 transcription involved in the transcriptional initiation of IFNs‐I.…”
Section: Fundamental Medicinal Properties Of Rice Branmentioning
confidence: 99%
“…Pigmented or colored rice with its bran is known to contain high contents of nutrients and phytochemicals that have potential health benefits, such as the ability to prevent chronic non-communicable diseases [ 10 ]. Rice bran, especially red and purple/black rice bran, reportedly has beneficial properties, such as metabolic-improving, anti-inflammatory, and antioxidant properties, possibly due to the presence of phenolic compounds such as proanthocyanidins, anthocyanins, protocatechuic acids, γ-oryzanols, vitamin E, and coenzyme Q10 [ 10 , 11 , 12 , 13 , 14 ]. We reported in our previous study that red rice bran extract (RRBE) improves glucose-insulin homeostasis by up-regulating insulin-signaling gene expression in the hepatic, adipose, and muscle tissues of obese mice [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…We reported in our previous study that red rice bran extract (RRBE) improves glucose-insulin homeostasis by up-regulating insulin-signaling gene expression in the hepatic, adipose, and muscle tissues of obese mice [ 15 ]. Moreover, RRBE, along with phenolic compounds, flavonoids, and their subclasses, has inhibitory effects on the production of inflammatory markers and genes in the adipose tissues of obese mice and inhibits macrophages, likely by affecting the expression of NF-κB pathway genes and stimulators of the interferon gene (STING) signaling pathway, respectively [ 11 , 12 ]. Also, other rice varieties such as purple rice and brown rice bran have been reported to exhibit anti-dyslipidemic and antioxidant properties in HFD-fed animals [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%